Reasons and Features of Patients Who Leave the Emergency Department Without Being Seen - Fahad Abuguyan; Abdulaziz Alhusainy; Omar Alsuliman; Sarah Alqahtani; Abdulrahman Alrajhi (Emergency Medicine International)
Conclusion: We conclude that in our center, prolonged waiting time and ED overcrowding are the main reasons why patients leave the ED without seeing a physician. Younger patients are more prone to LWBS, with trauma and gastroenterological complaints being the most common presenting symptoms. The LWBS rate was 3.81% of the total ED visits during the study period.